Quantum Interaction 5th International Symposium, QI 2011, Aberdeen, UK, June 26-29, 2011, Revised Selected Papers - Song, Dawei; Melucci, Massimo; Frommholz, Ingo.; Zhang, Peng.; Wang, Lei.; Arafat, Sachi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Symposium on Quantum Interaction, QI 2011, held in Aberdeen, UK, in June 2011. The 26 revised full papers and 6 revised poster papers, presented together with 1 tutorial and 1 invited talk were carefully reviewed and selected from numerous submissions during two rounds of reviewing and improvement. The papers show the cross-disciplinary nature of quantum interaction covering topics such as computation, cognition, mechanics, social interaction, semantic space and information representation and retrieval.
Keywords: Computer science; Information theory; Computer software; Electronic data processing; Artificial intelligence; Computer Science; Theory of Computation; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).; Mathematics of Computing; Computing Methodologies